2007
DOI: 10.1200/jco.2006.07.8170
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Pharmacokinetics, and Efficacy of AMG 706, an Oral Multikinase Inhibitor, in Patients With Advanced Solid Tumors

Abstract: In this study of patients with advanced refractory solid tumors, AMG 706 was well tolerated and displayed favorable pharmacokinetics and evidence of antitumor activity. Additional studies of AMG 706 as monotherapy and in combination with various agents are ongoing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
124
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(150 citation statements)
references
References 24 publications
24
124
0
2
Order By: Relevance
“…Motesanib (AMG 706) is a small molecule inhibitor of VEGF receptors (VEGFR) 1, 2, and 3, platelet-derived growth factor receptor (PDGFR), and stem cell factor receptor (c-Kit) which is administered orally (Rosen et al, 2007). Motesanib has clinical advantage compared to bevacizumab, because of its wide mechanism of action with inhibition of VEGF targets.…”
Section: Effects Of a Multikinasementioning
confidence: 99%
“…Motesanib (AMG 706) is a small molecule inhibitor of VEGF receptors (VEGFR) 1, 2, and 3, platelet-derived growth factor receptor (PDGFR), and stem cell factor receptor (c-Kit) which is administered orally (Rosen et al, 2007). Motesanib has clinical advantage compared to bevacizumab, because of its wide mechanism of action with inhibition of VEGF targets.…”
Section: Effects Of a Multikinasementioning
confidence: 99%
“…In a previous phase 1, dose-finding study of motesanib diphosphate in 71 patients with advanced solid tumours, five patients (7%) achieved a partial response and 35 (49%) stable disease [5]. Three of the five responders had advanced thyroid cancer.…”
Section: To the Editormentioning
confidence: 88%
“…In a phase I open-label, dose-escalating study, motesanib administered at the MTD of 125 mg po qd showed activity in patients with advanced solid tumors (sarcoma, kidney, lung, colon, ovarian, thyroid and other), with a disease control rate of 56%, and stabilization for more than 6 months in 23% of the cases [53].…”
Section: Motesanibmentioning
confidence: 99%